BANYU PANGURIPAN TRADITION: SACREDNESS IN AN ISLAMIC CONTECT - Afiliasi Ilafi; Bani Sudardi; Slamet Subiyantoro; Titis Srimuda Pitana (International Conference on Humanity Education and Society (ICHES), 2024)
The implementation of the Banyu Panguripan Tradition still balances the values of Islamic teachings that live in the community of Pulosari Subdistrict. Although this tradition has potential as a cultural tourism destination, it still does not leave the essence of the sacredness of this tradition. The Banyu Panguripan tradition is a tradition related to springs and water sources, which is not only in Pulosari Subdistrict. But some areas also have the same tradition, such as in Kudus. The difference lies in the packaging and implementation of the event. The use of descriptive qualitative methods is considered appropriate in this research because the techniques used in data collection are observation and interviews so that the data obtained comes from interviews with informants who are relevant and credible to this research. The sacredness that exists in the implementation of the Banyu Panguripan Tradition still does not leave the Islamic corridor in the community.